A new clade of styrene monooxygenases for (R)-selective epoxidation. Issue 6 (22nd January 2021) - Xiao, Hu; Dong, Shuang; Liu, Yan; Pei, Xiao-Qiong; Lin, Hui; Wu, Zhong-Liu
Abstract : Styrene monooxygenases (SMOs) are excellent enzymes for the production of ( S )-enantiopure epoxides, but so far, only one ( R )-selective SMO has been identified with a narrow substrate spectrum. Abstract : Styrene monooxygenases (SMOs) are excellent enzymes for the production of ( S )-enantiopure epoxides, but so far, only one ( R )-selective SMO has been identified with a narrow substrate spectrum. Mining the NCBI non-redundant protein sequences returned a new distinct clade of ( R )-selective SMOs. Among them, Se StyA from Streptomyces exfoliatus, Aa StyA from Amycolatopsis albispora, and Pb StyA from Pseudonocardiaceae were carefully characterized and found to convert a spectrum of styrene analogues into the corresponding ( R )-epoxides with up to >99% ee. Moreover, site 46 ( Aa StyA numbering) was identified as a critical residue that affects the enantioselectivity of SMOs. Phenylalanine at site 46 was required for the ( R )-selective SMO to endow excellent enantioselectivity. The identification of new ( R )-selective SMOs would add a valuable green alternative to the synthetic tool box for the synthesis of enantiopure ( R )-epoxides.